Development of Interactive E-Modules Based on Kvisoft Flipbook with Discovery Learning Models on Arthropod Material to Improve Student Learning Outcomes - Hasibuan, Syarifah Hanum; Zulfarina, Zulfarina; Putra, Riki Apriyandi (FKIP - Universitas Riau, 2023)
Education is a learning activity that determines the success of achieving student learning outcomes in class. So, to achieve learning goals by increasing student learning outcomes, it is necessary to have a good and correct learning process with the help of facilities, good learning methods.This study aims to determine the effect of an interactive e-module based on kvisoft flipbook with the discovery learning model on arthropod material on student learning outcomes. This research uses development research (R&D) with the ADDIE model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. This research reached the evaluation development stage. Phase testing for e-module development in the form of validation (media expert, material expert and pedagogic expert) and testpracticality and student response. The results of the validation analysis are in the very valid category. Practicality is in the very practical category used in learning, and student responses are in the very good category and are well received by students in learning.